Changes in tremor and hormonal responses to high-intensity exercise on kayak ergometer - Gajewski, J.; Sitkowski, D.; Obminski, Z. (Biology of Sport, 2006)
The aim of this study was to detect possible relationships between cortisol and testosterone concentrations and the exercise-induced changes in tremor. Twelve male kayakers, members of the National Team were subjected to routine physiological tests and tremor measurements. Specific kayak ergometer tests consisted of 3 submaximal bouts of increasing intensity lasting 4 min each followed by a 4-min maximal bout. Plasma levels of testosterone and cortisol were determined in capillary blood samples. Tremor was measured accelerometrically before the test and then 10 and 30 min after the last bout. It was demonstrated that the most significant post-exercise changes in tremor amplitude concerned mainly the 10-20 Hz frequency range. There were no signs of tremor recovery even 30 min after the exertion. A close relationship between cortisol and testosterone concentrations and changes in the high-frequency tremor amplitude was demonstrated. High testosterone concentrations were associated with higher changes in tremor amplitude, while high cortisol concentrations seemed to restrict this increase and to prolong simultaneously tremor recovery.